Pilot investigation of the rhizosphere microbial communities and metabolism of two cultivars of Polygonatum cyrtonema Hua - Liu, Fang; Dong, Wenlong; An, Yi; Qian, Hongyu; Gui, Chunlin; Xu, Yunjian (Frontiers in Microbiology, 2025)
Polygonatum cyrtonema Hua, a medicinal herb valued in traditional Chinese medicine, produces bioactive polysaccharides and saponins, exhibits intraspecific metabolic variations whose interactions with rhizosphere microbiota remain unexplored. As a pilot investigation, we characterized these linkages in two representative high-yield cultivars (JH1: bead-like tubers; JH2: L-shaped rhizomes) through integrated 16S rRNA/ITS sequencing and metabolomics. Bacterial communities showed conserved composition (Proteobacteria-dominated; shared core genera Candidatus Koribacter and Bradyrhizobium), whereas fungal assemblages diverged sharply between cultivars. JH1 rhizospheres enriched Hydnum, Collimyces, Ramariopsis and Coralloidiomyces, whereas JH2 favored Acremonium, Archaeospora, Didymosphaeria, Entoloma and Monacrosporium. Metabolomic profiling revealed tissue-driven specialization as the primary determinant, with tubers accumulated oleoyl ethylamide/DL-malic acid and roots preferentially storing DL-arginine. The core bacteria exhibited consistent negative association with organ-specific metabolites, whereas, fungal interactions diverged. JH1 enriched fungi positively associated with tuber oleoyl ethylamide and root DL-arginine but negatively with tuber DL-malic acid, while JH2-enriched taxa showed inverse relationships. The enriched fungal communities (average positive correlation coefficient 0.39) demonstrated stronger tissue-specific metabolite coordination than bacteria (average positive correlation coefficient 0.15), suggesting potential mycobiome-mediated regulation of medicinal compound partitioning. This preliminary dissection of cultivar-associated microbial-metabolite interplay may provide a mechanistic framework for optimizing P. cyrtonema cultivation through synthetic microbial consortia. However, future multi-location, multi-season studies with soil controls are needed to validate ecological generality.